Antioxidant and photoprotective potential of moringa oleifera lam (Moringaceae) - Gimenis, Janine Mailho [UNESP]; Gomes, Amanda Costa [UNESP]; Dos Santos, Valter Henrique Marinho; Ferreira, Paulo Cesar; Oliveira, Camila Areias; Baby, André Rolim [UNESP]; da SILVA, Regildo Márcio Gonçalves [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
Moringa oleifera Lam. (Moringaceae) is a plant with several biological activities and therapeutic properties. However, the complete knowledge about its pharmacological, biological and ecological effects, and about the active components present in each vegetable part are not still completely elucidated. This study aimed to evaluate the antioxidant and photoprotective activities of different extracts from leaves and flowers of M. oleifera. These activities were assessed through in vitro tests, DPPH radical scavenging method, iron ion chelating effect (FRAP), lipid peroxidation (TBARS), nitric oxide scavenging method and assessment of the activity against the lipid peroxidation through hemolytic method. The photoprotective activity was assessed through spectrophotometric analysis and through in vitro test with Labsphere. It was also determined the extract’s phenolic content and total flavonoid through spectrophotometry and HPLC. The obtained results demonstrated that this species have components with antioxidant and photoprotective potential mainly in the extracts obtained from fresh leaves and flowers. Therefore, it was possible to verify that M. oleifera has potential to be used as source of antioxidant components with photoprotective activity mainly due to the presence of phenolic components and among these, the flavonoids.
Potencial antioxidante e fotoprotetor de moringa oleifera lam (Moringaceae)
Keywords: Flavonoids; Formulations; Moringa oleífera; Plant-based cosmetics; Sunscreen; Vegetables